PENENERAPAN KONSEP MARKETING PUBLIK RELATIONS SEBAGAI STRATEGI PEMASARAN POLITIK DALAM KAMPANYE POLITIK - Yunidyawati Azlina (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The article in this article is about the form of marketing public relations (MPR) applied in political campaigns in Indonesia. This article focuses more on seeing how the MPR concept is applied in modern political campaigns. The data presented is the use of secondary data which is presented in the form of descriptive analysis. The research method used in this study is observation. From this paper shows the benefits of the concept of Marketing Public Relations in modern political campaigns in Indonesia.